2016
DOI: 10.36834/cmej.36779
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound as a competency for general internists: a survey of internal medicine training programs in Canada

Abstract: Background: Point-of-care ultrasound (POCUS) is increasingly used on General Internal Medicine (GIM) inpatient services, creating a need for defined competencies and formalized training. We evaluated the extent of training in POCUS and the clinical use of POCUS among Canadian GIM residency programs.Method: Internal Medicine trainees and GIM Faculty at the University of Toronto were surveyed on their clinical use of POCUS and the extent of their training. We separately surveyed Canadian IM Program Directors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Following this acknowledgement from the ACP, the Society of Hospital Medicine issued a similar position statement highlighting their support for the use of POCUS by hospitalists [5]. Nationally and internationally, POCUS is increasingly incorporated in IM residency training programs over the last decade [7][8][9][10][11]. Recognizing the importance of POCUS in medical education, the Alliance of Academic Internal Medicine supports the integration of POCUS across the training continuum [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this acknowledgement from the ACP, the Society of Hospital Medicine issued a similar position statement highlighting their support for the use of POCUS by hospitalists [5]. Nationally and internationally, POCUS is increasingly incorporated in IM residency training programs over the last decade [7][8][9][10][11]. Recognizing the importance of POCUS in medical education, the Alliance of Academic Internal Medicine supports the integration of POCUS across the training continuum [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing appetite for POCUS training, progress in expanding POCUS in IM has been slow. A major obstacle to the expansion of POCUS training is a lack of skilled faculty, and previous studies have cited limited time, money and resources as the key barriers to faculty adoption of POCUS [7,11,[13][14][15][16][17][18]. A more nuanced understanding of perceived faculty barriers is needed, however, to allow for more targeted interventions.…”
Section: Introductionmentioning
confidence: 99%
“…GPs were asked to identify the clinical indications for which they presently utilize or anticipate using ultrasound for adult patients. An extensive list of indications was created based on previous surveys, published literature, and the clinical conditions targeted by POCUS according to the SGUM model [7,8,14,[19][20][21]. POCUS indications were not highlighted but blended in the list.…”
Section: Cross-sectional Survey Datamentioning
confidence: 99%
“…9 Internal medicine (IM) is similarly gaining PoCUS interest, with approximately 30-50% of IM residents using PoCUS. 10,11 A nationwide survey found that only 25% of IM programs have formal PoCUS education, with many curricula limited to USguided central venous cannulation. 10 We recently published that while 27% of IM residents are using PoCUS to guide clinical decision-making, only 9.7% of residents have formal PoCUS training.…”
Section: Résultatsmentioning
confidence: 99%
“…10,11 A nationwide survey found that only 25% of IM programs have formal PoCUS education, with many curricula limited to USguided central venous cannulation. 10 We recently published that while 27% of IM residents are using PoCUS to guide clinical decision-making, only 9.7% of residents have formal PoCUS training. 11 As with any tool, there is a risk of causing more harm than benefit with inadequate training.…”
Section: Résultatsmentioning
confidence: 99%